Crossing the Water and Keeping the Faith : Haitian Religion in Miami - Rey, Terry (Book collections on Project MUSE., 2016)
A historical and ethnographic study of Haitian religion in immigrant communities, based on fieldwork in both Miami and Haiti, as well as extensive archival research.